2012
DOI: 10.1097/nhh.0b013e31824c28bd
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Medication Self-Management Errors in Older Adults Discharged Home from a Community Hospital

Abstract: The purpose of this article is to report the results of a pilot study of the relationship between cognitive impairment and medication self-management errors in older adults discharged home from a community hospital. It is hoped that these preliminary data will provide some new ideas for reducing errors in medication self-management posthospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…While the rate of re-hospitalization was found to be lower in patients visited at their homes, it was higher in patients who had not given consent and those who could not be contacted (40). Moreover, the results indicate that rehospitalization is associated with previous re-hospitalization, low social support, depression, poor drug compliance, and late visit from the family physician (41,42).…”
Section: How Can High-risk Patients Be Detected?mentioning
confidence: 70%
“…While the rate of re-hospitalization was found to be lower in patients visited at their homes, it was higher in patients who had not given consent and those who could not be contacted (40). Moreover, the results indicate that rehospitalization is associated with previous re-hospitalization, low social support, depression, poor drug compliance, and late visit from the family physician (41,42).…”
Section: How Can High-risk Patients Be Detected?mentioning
confidence: 70%
“…However, when patients report that they are not managing their medication correctly, there is good reason to believe this is true (Roth & Ivey, 2005). Hain et al (2012) reported that 13% of the participants responded they were having difficulty taking their medications during telephone interview; however, about 52% were found to have one or more medication discrepancies by home visit. It is well established that patient self-reporting of nonadherence lacks sensitivity but has high specificity; in other words, when patients report that they are not managing their medications correctly, there is good reason to believe this is true (Roth & Ivey, 2005).…”
Section: Medication-related Problems After Hospital Dischargementioning
confidence: 93%
“…Polypharmacy is a growing problem, often combined with complex instructions such as having to manage more than one medication (Hain et al, 2012) and taking medications more than once a day (Beckman et al, 2005), which increases the difficulty in mediation self-managing for older patients. Second, polypharmacy may increase the risk of adverse drug reactions and contribute to costs (Ballentine, 2008), which would lead to nonadherence (Ownby, 2006).…”
Section: Predictors Of Medication-related Problemsmentioning
confidence: 99%
See 2 more Smart Citations